Examining the technical efficiency of small industries: A case study of the crackers industry in South Sumatera, Indonesia - Mukhlis Mukhlis (Department of Development Economics, Universitas Sriwijaya, 2020)
Small industries are life-sustaining for communities because of their political and strategic position in terms of creating job opportunities and increasing revenue. One small industrial sector that has the potential to be developed is the food industry. Small food industries are widely scattered in every area, including in the city of Palembang. A small industrial group of food that became one of the culinary icons in Palembang is the cracker industry. This type of industry is a culinary icon that has been famous for foreign countries. Nevertheless, the cracker industry is still experiencing obstacles in terms of capital and marketing. The cost of raw materials is relatively expensive to technically trigger the industry inefficiencies. Therefore, it is necessary to review the technical efficiency of this small industry. The variables used in this study were capital, labor, and output. The data used is secondary data that is analyzed by using the Stochastic Frontier Analysis (SFA) approach. The results showed that the technical efficiency achievement of small industrial crackers in South Sumatera is still categorized as low. The use of labor input is more effective than capital use as a result of the utilization of technology and local resources. Therefore, the development of small industrial crackers through an efficiency approach cannot be separated from the application of technology, human resource management, marketing, and business climate.